Cadmium Exposure Alters Rhizospheric Microbial Community and Transcriptional Expression of Vetiver Grass - Wu, Bin; Li, Jia; Peng, Dinghua; Wang, Ziru; Xu, Heng (Frontiers in Plant Science, 2022)
Vetiver grass (Chrysopogon zizanioides L.) has been used to remediate cadmium contaminated soil, while there have been few studies on the influence of cadmium exposure on the rhizospheric microbial community and transcriptional expression of C. zizanioides. In this study, we investigated the response of rhizospheric microbial community and transcriptional expression of C. zizanioides in 20 mg/kg cadmium contaminated soil. The results showed that cadmium levels in the roots and shoots of C. zizanioides reached 250.80 and 73.40 mg/kg, respectively. The cadmium exposure changed the rhizospheric bacterial community, resulting in significant enrichment of Sphingomonas, Lysobacter, and Gemmatimonadetes in cadmium contaminated soil. In addition, 880 and 3419 differentially expressed genes were identified in the plant roots and shoots, respectively, in response to cadmium stress. Among these, the overexpressed genes associated with redox homeostasis, glutathione (GSH) metabolism, cell wall biosynthesis, and transmembrane transport pathways were found to participate in cadmium detoxification in C. zizanioides. These findings could be useful for understanding the selective variation of rhizospheric microbial community and detoxification mechanisms of C. zizanioides in cadmium phytoremediation.